Pemberian Buah Merah (Pandanus conoideus Lam) sebelum Dipapar Timah Hitam Menekan Ekspresi Caspase-8 dan Jumlah Sel Hofbauer Mencit (Mus musculus) Bunting (THE PROVISION OF RED FRUIT (Pandanus conoideus Lam) BEFORE EXPOSED BY LEAD DECREASE EXPRESSION OF C - Wahyuni, Ika; Widjiati, Widjiati; Madyawati, Sri Pantja; Rantam, Fedik Abdul (Jurnal Veteriner; Vol 18 No 1 (2017), 2017)
The research aims to observed the provision of red fruit in placenta pregnat mice before exposed by lead. The observed case are expression of caspase-8 and number of hofbauer cells. Red fruit was expected to decrease expression of caspase-8 and number of hofbauer cells. The study design used was complete randomized design. Each treatment utilized four pregnant mice as negative control group (K-), for this group given distilled water orally during gestation 6 th -15 th . Positive control group (K+) given lead (0.011mg/20 g BW in 1 mL distilled water) orally during gestation 6 th -15 th . The treatment group namely P1, P2, and P3 treated by red fruit with different doses i.e., 8.29 mg/20 g BW, 23.98 mg/20 g BW, and 25.68 mg/20 g BW, respectively, during gestation 6 th -15 th , then one hour later exposed with lead. The obtained data were analyzed by Kruskal-Wallis and Mann Whitney test for calculate caspase-8 expression, ANOVA and Duncan for calculate the number of hofbauer cells. The result indicated that treatment groups which provided by red fruit of 0.8 mL/20 g BW and 0.9 mL/20 g BW showed decline expression of caspase-8 and number of hofbauer cells compare control group without admission of red fruit antioxidant and P1. Inconclusion red fruit can decrease expression of caspase-8 and number of hofbauer cell that means decrease apoptosis. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh pemberian buah merah pada plasenta mencit bunting sebelum dipapar timah hitam. Variabel yang diamati adalah ekspresi caspase -8 dan jumlah sel hofbauer . Buah merah dapat menurunkan ekspresi caspase-8 dan jumlah sel hofbauer . Penelitian ini menggunakan rancangan acak lengkap (RAL). Setiap kelompok perlakuan menggunakan empat mencit bunting sebagai kelompok kontrol negatif (K-), untuk kelompok ini diberi aquades pada kebuntingan hari ke-6 sampai 15. Kelompok kontrol positif (K+) diberi timah hitam dosis 0,011 mg/20 g BB dalam 1 mL aquades selama kebuntingan hari ke-6 sampai 15. Kelompok perlakuan (P1, P2, dan P3) diberi minyak buah merah dengan dosis yang berbeda yaitu 8,29 mg/20 g BB, 23,98 mg/20 g BB, dan 25,68 mg/20 g BB. Data dianalisis dengan Kruskall-Wallis dan Mann Whitney untuk menghitung ekspresi caspase -8, sidik ragam dan uji Duncan digunakan untuk menghitung jumlah sel hofbauer. Hasil penelitian menunjukkan kelompok perlakuan yang diberi buah merah 23,98 mg/20 g BB dan 25,68 mg/20 g BB dapat menurunkan ekspresi caspase -8 dan jumlah sel hofbauer dibandingkan dengan kelompok kontrol positif dan P1. Simpulan penelitian ini adalah bahwa minyak buah merah dapat menurunkan ekspresi caspase -8 dan jumlah sel hofbauer yang berarti menekan terjadinya apoptosis.
Keywords: lead; red fruit; caspase-8; hofbauer cell